ESRA19-0394 Serratus plane block/lateral cutaneous branches of the intercostal nerves in the mid-axillary line block for radical mastectomy in a high risk patient. (30th August 2019) - Lorenzo, YF; Martín, M; de la Quintana, B; de Castro, C; Silva, L; Rojas, R
Abstract : Background and aims: The SPB/BRILMA block was described in 2013 as a good method for multimodal analgesia in non-reconstructive breast surgery. Methods: A 94-year-old woman, ASA III, was listed for a left radical mastectomy because of an ulcerated breast cancer. It was a painful, infected and malodorous ulcer. She presented severe medical comorbidities and was under many medications. 2 mgr of midazolam were administrated before performing the BRILMA block under ultrasound vision, using a 50-mm ultra-plex needle (20 mL of bupivacaine 0.125% were introduced into the fascial plane between the serratus anterior muscle and the external intercostal muscle at the level of the 3rd, 4th and 5th ribs). After that, an intravenous induction with 70 mgr of propofol and 100 µgr of fentanyl was performed and an I-gel® LMA was placed. She received sevoflurane® (CAM 0.5) for the maintenance of anesthesia. Results: The patient was successfully treated under BRILMA block. She maintained a good hemodynamic stability during the procedure and was extubated without any complications. She did not need any other analgesics during the surgery. During the first 24 hours the patient did not request opiates, and she just received alternately 1 gr of acetaminophen and 2 gr of metamizol as a part of our multimodal analgesic guideline. Conclusions: The SPI/BRILMA block by ultrasound can be used for intra and post-operative analgesia for non-reconstructive surgery providing good postoperative pain control which allows a reduction of the use of opiates. It could be also used as an alternative to general anesthesia and loco-regional conventional techniques in high risk patients.